Study protocol of a pilot study evaluating feasibility and acceptability of a psychosexual intervention for couples postallogeneic haematopoietic stem cell transplantation. Issue 10 (31st October 2020) - Pillay, Brindha; Ftanou, Maria; Ritchie, David; Panek-Hudson, Yvonne; Jefford, Michael; Garcia, Teresa; Shields, Cassandra; Gniel, Jo; Phipps-Nelson, Jo; Drosdowsky, Allison; Blaschke, Sarah; Ellen, Steve
Abstract : Introduction: Sexual dysfunction is one of the most common side effects of allogeneic haematopoietic stem cell transplantation (HSCT) for haematological cancers. Problems can persist between 5 and 10 years post-transplant and impact mood, couple intimacy and relationship satisfaction. Few intervention studies, however, target sexual dysfunction in patients post-HSCT. This pilot study aims to examine the feasibility and acceptability of implementing a psychosexual intervention for HSCT survivors and their partners post-transplantation. Methods and analysis: Fifteen allogeneic HSCT survivors and their partners will be recruited. Patients who are more than 3 months post-transplantation will be sent invitation letters describing the couples' psychosexual intervention that will be offered through this study. The intervention will comprise two components: (1) psychosexual education about medical and behavioural treatment options for sexual dysfunction delivered by a haematology nurse consultant; (2) emotionally focused therapy-based relationship education programme for couples delivered by a clinical psychologist (four sessions of 1.5 hours each). Couples who consent to participate will be administered a series of measures assessing mood, relationship satisfaction and sexual dysfunction preintervention and post-intervention, as well as satisfaction with the intervention postintervention. Feasibility of the intervention will be examined via recording enrolment rate, adherence, compliance with completing outcome measures and fidelity of intervention delivery. Ethics and dissemination: Ethics approval has been obtained at the Peter MacCallum Cancer Centre in Melbourne, Australia. Results will be presented at national and international conferences and published in a peer-reviewed journal so that in can be accessed by clinicians involved in the care of allogeneic HSCT patients. If this intervention is found to be feasible and acceptable, its impact will be examined in a future randomised controlled trial and subsequently implemented as part of routine care in the allogeneic HSCT population.